The Relationship between C-Reactive Protein (CRP) Levels and HbA1c Levels in Type II Diabetes Mellitus Patients - Utami, Rinda; Susanto, Zaenal Adi; Marsudi, La Ode; Maulida , Shofia; Mustofa , Khalid (Journal of Indonesian Medical Laboratory and Science, 2025)
Background: Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action, or both. Type II diabetes mellitus is caused by the pancreas gland being unable to meet the body's insulin needs. The HbA1c test reflects the average blood glucose level for 2-3 months or about 120 days before the test. C-reactive protein (CRP) is an inflammatory biomarker that is often used to assess the level of systemic inflammation. Elevated CRP levels have been associated with insulin resistance, endothelial dysfunction, and the development of atherosclerosis, all of which contribute to complications in diabetic patients. Therefore, further research is needed to evaluate the correlation between HbA1c and CRP levels, to better understand the relationship between glycemic control and systemic inflammation. Objective: This study aims to determine the relationship between C-reactive protein (CRP) levels and HbA1c levels in patients with Type II Diabetes Mellitus. Materials and Methods: This study used purposive sampling technique and analytic survey with cross-sectional approach. Results:  Data analysis using the Chi-Square test obtained a p-value of 0.536, where if Sig> 0.05 then it shows there is no significant relationship. So, there is no relationship between C-reactive protein (CRP) levels and HbA1c levels in Type II Diabetes Mellitus patients.